Forage production for smallholder farmers in a rainfed millet cropping system in central Mali - Bartholomew, P.W.; Ly, R.; Koné, D.; Traoré, S.F.; Sissoko, K. (Cambridge University Press, 1992)
A shortage of available labour early in the growing season, when effort is directed to the weeding of cereal crops, appeared to be a primary constraint to increased forage cropping by smallholder farmers in the semi-arid zone of central Mali. In experiments with millet, the labour requirement for weeding was reduced by an average of 45 percent when the crop was weeded at two rather than four weeks after emergence. A combination of weeding by hand and by ox-drawn plough or harrow only slightly increased labour productivity compared with hand weeding alone. Both lablab and cowpea produced good yields of forage when sown in mid-July, but average yield declined by 71 kg ha-1 for each day's delay in sowing between mid-July and mid-August. Green gram was also productive over a two month growing period and appeared to have potential as a late-sown forage crop.